Antipsicóticos atípicos no tratamento da irritabilidade severa em crianças e adolescentes com perturbação do espectro do autismo: Uma Revisão - Ana Cláudia Herdeiro Vaz de Moura (2020)
Abstract Autism spectrum disorder is a brain-based neurodevelopmental disorder characterized by impairments in social communication and by the presence of restricted, repetitive patterns of behaviour and interests. It has its onset in early childhood and significantly impacts the children and the family lives. Irritability and aggression are common co-occurring psychiatric conditions in autism spectrum disorder (25%) and the usage of atypical antipsychotics might be considered. The goal of the present review is to analyse the short and long-term efficacy and safety of risperidone, aripiprazole and paliperidone in the treatment of irritability in children and adolescents with autism spectrum disorder. A literature review was performed, searching PubMed and Cochrane Database of Systemic Reviews, using the Medical Subject Headings. The studies considered in this review show their efficacy in the short and long-term treatment. Although atypical antipsychotics have a safer profile than typical antipsychotics, they are associated with a significant weight gain and metabolic complications that shouldn't be overlooked. During antipsychotic treatment, it would be prudent to conduct a metabolic screening and implement preventive measures such as a calorically appropriated diet and physical exercise to reduce weight gain. In conclusion, the use of antipsychotics should be reserved for severe and enduring cases of irritability, when behavioural interventions have been tried and failed and when harm to self and others imminently exceeds the risk of harm from medication.